Meredam Polarisasi Politik di Era Jokowi: Pendekatan Diskursus Deliberatif Jürgen Habermas - Marselinus Langgor; Aldofus Leba; Felix Riondi Sugar; Adelberto Wili Boko; Ikordinus P. Wasini; Fridolin Mawangsuri Fallo; Yohanes Reinaldi Lagang; Yohanes Prasesko Djegaut (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2026)
This article examines the phenomenon of political polarization in Indonesia during President Joko Widodo’s administration, which has been intensifying, particularly in the context of elections and social media dynamics. This polarization is characterized by the division of society into groups that are ideologically, politically, and socially opposed to one another, which in turn threatens social cohesion and democratic stability. This study employs a qualitative method with a literature review approach to analyze the dynamics of political polarization and offers normative solutions through Jürgen Habermas’s theory of deliberative discourse. The findings indicate that political polarization in Indonesia is influenced by intense electoral contests, the politicization of identity, and the spread of disinformation in the digital sphere. In this context, Habermas’s theory of deliberative democracy offers an alternative approach by emphasizing the importance of an inclusive public sphere, rational dialogue, and citizen participation in the policy-making process. This approach focuses not only on political outcomes but also on fair and reflective communication procedures to achieve consensus. This article concludes that strengthening the deliberative public sphere, political education, digital literacy, and the ethics of public communication can serve as effective strategies to mitigate political polarization in Indonesia.